Lanthanides and actinides: Annual survey of their organometallic chemistry covering the year 2019 - Farnaby, Joy H.; Chowdhury, Tajrian; Horsewill, Samuel J.; Wilson, Bradley; Jaroschik, Florian (Coordination chemistry reviews, 2021)
•Dinitrogen activation and transformation with low-valent complexes.•Divalent lanthanide complexes as interesting single molecular magnets.•Heterobimetallic complexes from reactions with transition metal precursors.•Synthesis and characterization of new endohedral metallofullerenes.•Full characterization of organoamericium(III) compound Am(C5Me4H)3. This review summarizes the progress in organo-f-element chemistry during the year 2019. Organo-f-element chemistry, including Sc, Y, the lanthanides and the actinides, has been a flourishing research area for many years. The mainly ionic and Lewis acid character of the lanthanide metals provides a vast array of intriguing structural features supported by numerous organic ligands. In this year’s edition several new types of complexes are presented, including the first scandacyclopropene complex [Cp*(BuC(NiPr)2)Sc(η2-PhCCPh)][K(crypt)] displaying an aromatic metallacycle, the first lanthanide-aluminabenzene complexes [(1-Me-3,5-tBu2-C5H3Al)(μ-Me)Ln(2,4-di-tbutylpentadienyl)] (Ln = Y, Lu) and the first scandium phosphonioketene complex [LSc(η2-COCHPPh3)I] (L = [MeC(NDIPP)CHC(NDIPP)Me−], which all showed interesting reactivities. Furthermore, a wide range of lanthanide alkyl complexes were synthesized and structurally characterized, including the first isolated ScMe3 derivatives [Sc(AlMe4)3(Al2Me6)0.5] and [(Me3TACN)ScMe3]. A very important finding in divalent lanthanide chemistry was the synthesis of the first neutral divalent Dy and Tb sandwich complexes, Ln(C5iPr5)2, which were investigated for their magnetic properties. The reactivity of divalent metallocenes towards transition metals precursors or As0 provided unprecedented multimetallic complexes, for example [(Cp*2Sm)4As8], [{(Cp*)2Sm}3{(μ-O4C4)(μ-η2-CO)2(μ-η1-CO)(CO)5Re2}SmCp*2(thf)] and [Cp*2Yb(taphen)MMe2YbCp*2] (M = Ni, Pt; taphen = 4,5,9,10-tetraazaphenanthrene). New reactivity of lanthanide complexes was unveiled, such as the direct dinitrogen to hydrazine conversion using a low-valent Sc complex or the reduction of CS2 using different divalent Yb complexes affording for the first time a CS22− bridging unit as shown in the complex [Yb2(DippForm)4(CS2)] or an intriguing acetylendithiolate bridged Yb(III) complex Yb2L4(C2S2) (L = (OtBu)3SiO−). Numerous new lanthanide catalyzed homo- and co-polymerization processes involving polar or non-polar monomers were reported, including efficient and stereoselective polymerization of o-methoxystyrene, vinylpyridine or isoprene. The regio-, diastereoselective and stereoregular cyclopolymerization of different ether and thioether substituted 1,6-heptadienes was reported. A wide range of hydrofunctionalization reactions were developed, among them an efficient hydrophosphinylation process of styrenes and alkynes. It was further shown that alkyllanthanide halides could undergo efficient halogen/lanthanide exchange with arylhalides and vinylhalides providing useful organolanthanide transfer reagents, for example in the stereoselective Zweifel olefination. Organolanthanide complexes have also found new applications in material sciences, for example, Ce(C5H4iPr)3 was employed for the formation of an ultrathin CeO2 overlayer on a Pt electrode via atomic layer deposition to improve low-temperature solid oxide fuel cells. An increasingly studied field is the area of endohedral metallafullerenes (EMF) which gave rise to a large number of unprecedented lanthanide compounds with unusual cages, as well as dimetalfullerenes with interesting single molecular magnet (SMM) properties and new insights on direct Ln-Ln bonds. Hydrocarbyl complexes of the actinides continued to flourish, in spite of the challenges presented by synthesis and characterization. The first examples of structurally-characterized uranium(IV) homoleptic aryl complexes and transuranic hydrocarbyl Np(III) complex have been reported. An experimental and computational study has demonstrated that f-orbitals have a structure-directing role in overlap-driven covalency in carbene-stabilised metalla-allene complexes and 13C NMR shift has be shown to be a simple and direct probe of the actinide-carbon bond covalency in the acetylides. Small molecule activation chemistry has provided some unusual and important results, including a uranium(V) carbene complex coordinated end-on to dinitrogen and a stable dinuclear U(IV) dihydride complex which reacted with CO2 and CO/H2 to form methoxide and ultimately methanol. New ligands and binding modes resulted from actinide main group chemistry, with reports of the first examples of terminal η1-cyaarside ligands (CAs−), bridging diarsaallene (As = C = As)2− and trapped radical dianion of the phosphoethynolate (OCP2−) ligand. The bis-CptBu2 metallocene stablised thorium phosphinidene continued to demonstrate a wealth small molecule reactivity, including reductive coupling, heterocycle formation and E–H (E = P, N, C) bond activation. Two examples of U(II) complexes are reported, [K(crypt)][(C5Me4H)3U] and [K(crypt)][U(NR2)3] (R = SiMe3). The first direct assembly of a uranium tri-rhenium triple inverse sandwich complex was reported, both experimental and computation data are consistent with atypical Cp-bonding, with electron density redistributed from Re(I) to U(III). Isopropyl substituted cyclopentadienyl ligands have enabled the synthesis, reactivity and magnetic properties of U(III) metallocenes, including base-free cationic species. The first example of a monomeric thorium terminal dihyrido compound (CpAr5)(Cp*)ThH2(THF) (Ar = 3,5-tBu2-C6H3) has been synthesized. The full characterisation of the organoamericium(III) compound (C5Me4H)3Am provided a unique insight into Am-C bonding. The Th(IV)/Th(III) redox couple has been experimentally determined for a range of Th(IV) and Th(III) organometallics. The first uranium phosphaazaallene has been synthesized by reaction of a bis-phosphide complex with tert-butyl cyanide. Actinide EMFs continued to be an active area of research; molecular structures, synthetic and purification methodologies are reported. How best to computationally model the distinct properties of actinide EMFs was the subject of some debate. Thorium complexes have found application in catalysis, in the selective dihydroboration of nitriles, the hydroboration of imines and polymerization of isoprene.